Peningkatan Aktivitas Belajar Siswa Pada Pelajaran Matematika Tentang Prisma Dan Limas Melalui Strategi Problem Solving Siswa Kelas VIII SMP Negeri 3 Sawit Boyolali - Wulandari, Diah; , Prof. Dr. Budi Murtiyasa, M.Kom (2013)
This research aims to determine improvement of student learning activities in math class VIII student of SMP Negeri 3 Oil Boyolali. This study uses action research. The process of learning to use strategies of Problem Solving. Data collection techniques of observation, testing, field notes, interviews, and documentation. Analysis using interactive model. Results of this study demonstrate the application of Problem Solving strategies can improve student learning activities, learning activity indicators: 1) learning activities answer the initial condition 7 students (20%), the first cycle 9 students (25.71%), 17 second cycle students (48 , 57%), third cycle of 26 students (74.29%), 2) learning activities ask questions precondition 4 students (11.42%), the first cycle 8 students (22.86%), cycle II, 14 students (40 %), the third cycle of 27 students (77.14%), 3) learning activities precondition expression 6 students (17.14%), the first cycle of 11 students (31.43%), 19 second cycle students (54.29 %), the third cycle of 27 students (77.14%), 4) present the learning activities of students work the initial conditions 0 (0%), the first cycle 5 students (14.71%), 12 second cycle students (34.29%) , cycle III 25 students (71.43%), 5) learning activities about the task teacher initial conditions 19 students (54.29%), the first cycle of 23 students (65.71%), 25 students of second cycle (71, 43%), third cycle of 29 students (82.86%).